Perspectives on Pilgrimage to Folk Deities - Dhali, Rajshree (The international journal of religious tourism and pilgrimage, 2020)
The title Perspectives on Pilgrimage to folk deities' has been chosen to underline the pattern of the alternative religious spaces and their transformation over the centuries which is not yet explored much. The evolution and shaping of folk cults, associated religious processes, and their incorporation into high ritual Hinduism forms a very dynamic part of the cultural and the religious history of India. My paper explores the pilgrimage to Ramdevra in the Jaisalmer district of Rajasthan, India, where the main shrine of the folk deity Ramdev is located. He is a popular folk deity of the erstwhile untouchable communities and is currently considered a Pan Hindu God in Rajasthan. The historical evolution of the religious pattern of the deity in question has been outside the margins of the institutionalised religion, Hinduism, for a very long time, and only from the nineteenth century on has there been some infusion of the high ritual-religious pattern in its non-Brahmanical origins. The paper traces the dynamism of intermixing of the Brahmanical and the non-Brahmanical traditions at the main shrine at Ramdevra at the time of a large congregation during August-September, commonly referred to as Mela (fair). I make two main arguments in the paper: one, there is a growing influence and assimilation of Brahmanical rituals in the traditions of the Ramdev cult as well as an increased marginalisation of integral non-orthodox traditions associated with it at the pilgrimage site in the wake of the resurgence of Hindutva politics. I also argue that this sacred space contributes to a process of formation of solidarity in a subtle manner amongst the members of the Dalit community, the traditional followers of Ramdev.